2008
DOI: 10.1021/om800163p
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structures of Platinum(0) Alkyne Complexes with Extended π-Conjugated Systems

Abstract: 1,2-Bis[(2,4,6-tri-tert-butylphenyl)phosphinidene]cyclobuta[l]phenanthrene (DPCB-phen) as a low-coordinated phosphorus ligand forms the platinum(0) alkyne complexes [Pt(alkyne)(DPCB-phen)] with extended π-conjugated systems. The colors of the complexes are highly dependent on alkyne ligands, showing a marked variation from reddish orange to teal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…The plane of the five-membered ring in 2Os and 2Ir is parallel to the axial L–M–L plane (L axial –M–C1–C5 dihedral angle, θ, is 1.5 and 0.0°, respectively), while that of 2Re and 2Pt lies in between the axial (L–M–L) and the equatorial (L′–M–L′) planes of TBP geometry (L–M–C1–C5 dihedral angle, θ, is 29.6 and 14.6°, respectively). The calculated M–C1 bond lengths in 2M range from 1.970 to 1.885 Å, which are within the experimentally reported M–C double bond lengths , and are in between the M–C1 (1.871–1.790 Å) single and M–C5 triple bond lengths (2.163–2.041 Å) of 1M . The other isomers of 2M in which the five-membered ring is perpendicular to the axial ligands ( 2M′ , M′ = Re, Os, Ir) are higher-order saddle points (Figure ).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The plane of the five-membered ring in 2Os and 2Ir is parallel to the axial L–M–L plane (L axial –M–C1–C5 dihedral angle, θ, is 1.5 and 0.0°, respectively), while that of 2Re and 2Pt lies in between the axial (L–M–L) and the equatorial (L′–M–L′) planes of TBP geometry (L–M–C1–C5 dihedral angle, θ, is 29.6 and 14.6°, respectively). The calculated M–C1 bond lengths in 2M range from 1.970 to 1.885 Å, which are within the experimentally reported M–C double bond lengths , and are in between the M–C1 (1.871–1.790 Å) single and M–C5 triple bond lengths (2.163–2.041 Å) of 1M . The other isomers of 2M in which the five-membered ring is perpendicular to the axial ligands ( 2M′ , M′ = Re, Os, Ir) are higher-order saddle points (Figure ).…”
Section: Resultssupporting
confidence: 85%
“…The optimized geometrical parameters of 1Re and 1Os are close to the experimentally reported geometrical parameters of osmabenzyne , and rhenabenzyne . The calculated M–C1 (1.817–1.790 Å) and M–C5 (2.163–2.041 Å) bond lengths in 1M are within the range of metal–carbon triple and single bond lengths, respectively. ,, The six-membered C 5 H 4 M ring in 1M lies in the plane of L′–M–L′. The axial ligands in 1W and 1Pt are almost linear, with L–M–L bond angles of 176.8 and 175.8°, respectively.…”
Section: Resultssupporting
confidence: 74%
“…The HLG value of 6b (1.77 eV) was clearly lower than those of 4a (2.06 eV) and 4b (1.99 eV), and comparable to that of [Pt(tolan-NMe 2 )-(DPCB-phen)] having strongly electron-donating NMe 2 groups on the tolan-X ligand (1.82 eV). 8…”
Section: Methodsmentioning
confidence: 99%
“…More recently, we examined the electronic structures of [Pt(alkyne)(DPCB-phen)] complexes by UV-vis absorption spectroscopy and found the occurrence of extended p-conjugation among the platinum, alkyne and DPCB-phen ligand. 8 It was suggested that the p-conjugation involves dp-pp interaction between platinum and the out-of-plane p* of alkyne ligand (p > : the alkyne p* orbital perpendicular to the coordination plane), while such orbital interaction has been known to be insignificant in most cases, because the platinum dp orbital is occupied and undergoes repulsive interaction with the alkyne p > orbital. 9 We reasoned that donor-acceptor interaction 10 between the electron-rich pp system of alkyne and the electron-poor pp system of DPCB-phen facilitates the p-conjugation through the dp orbital of platinum.…”
Section: Introductionmentioning
confidence: 99%
“…While electrophilic activation of alkynes through π‐alkyne complex formation wit Pt has been studied extensively,1821 competition for complexation between a bidentate ( O, O' ) ligand system and an alkyne with Pt II has, to the best of our knowledge, not yet been reported in the literature. It was hoped that the presence of both an alkyne and ( O, O' ) moiety in one ligand, as in compound 5 , with the presented prospect of forming a kinetically stable 6 membered ring, through the malonate's coordination to platinum, would favourably compete for platinum coordination over that of the alkyne.…”
Section: Resultsmentioning
confidence: 99%